EDUKASI KESEHATAN TENTANG DAMPAK NEGATIF BULLYING DENGAN METODE EMO DEMO - Sallo, Glorya Injilika; Rakinaung, Natalia; Geneo, Martinus (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2024)
Introduction: The negative impact of bullying can cause a child to become depressed, lack of confidence, feelings of sadness, grief and distress as well as feel stupid and worthless so that their confidence is reduced and make them anxious in socializing with others. Objective: This study aims to determine the level of knowledge and attitudes of students in the prevention of bullying behavior in elementary school children. Method: The pre-experiment research design, using one group pre-post-test, uses a mix questionnaire instrument namely knowledge, attitude and behavior. The intervention provided was counseling using teaching aids. The population is elementary school children at SD XI Kristen Tandu in grades 4-6, Lolak District, Bolaang Mongondow Regency. The respondents totaled 25 people using the total sampling technique. The statistical test used was the paired t-test with a significant p-value of <0.05. Results: Through the Wilcoxon test, bullying knowledge showed p-value = 0.000. Bullying attitude shows p-value = 0.000. Bullying behavior shows p-value = 0.000. Conclusion: Health education about bullying in elementary school age children using the emo demo method is significantly effective in increasing the knowledge of elementary school children about the negative impact of bullying. The results of this study can add to the insight of teachers, parents and nurses about health education methods for elementary school age children, especially related to the negative impact of bullying behavior